(untitled) (Collection of scientific works «Modern structures of metal and wood», 2020)
Currently, the principles of adaptive architecture are most often used in the practice of building unique large-span spatial shell coverings. Constructed buildings and structures acquire artificial intelligence for economical and comfortable operation and can use computer programs to respond to changing environmental conditions. Such buildings and structures consist of structural systems capable of transforming to meet the needs of operation. The particular complexity of the design of transformable spatial structural systems is that their design scheme changes significantly during operation, and all numerous extreme changes must be predicted in advance. Structures that can change their geometric dimensions, that is, transform during operation, are considered in the article to solve the problems of adaptive architecture to create the proper microclimate inside buildings and structures. Only spatial structures consisting of elements of complex displacement in space were identified in the research, although there are many constructed transformable shells of coverings with a simpler transformation in space (horizontal, around a vertical axis, along the guiding support elements of the surface of the transfer shells). The development of such structures has many directions. One of the most difficult is the development of mobile structures in the space industry, when a large-sized structure packed in a container of minimum dimensions is delivered into orbit, and in orbit it automatically opens to the required dimensions. Modern approaches to the transformation of structures are given, which were highly appreciated during the new construction, reconstruction and operation of buildings and structures, and are promising for further research and application. For examples, spatial shell structures were used, as well as those operation and construction of which are carried out using computer programs. The analysis of the constructed shells of various shapes using pneumatic formwork to obtain mathematical models to determine the optimal overall dimensions and use in the design.